2015
DOI: 10.1002/2014gc005588
|View full text |Cite
|
Sign up to set email alerts
|

The mantle transition zone beneath West Antarctica: Seismic evidence for hydration and thermal upwellings

Abstract: Although prior work suggests that a mantle plume is associated with Cenozoic rifting and volcanism in West Antarctica, the existence of a plume remains conjectural. Here we use P wave receiver functions (PRFs) from the Antarctic POLENET array to estimate mantle transition zone thickness, which is sensitive to temperature perturbations, throughout previously unstudied parts of West Antarctica. We obtain over 8000 high-quality PRFs using an iterative, time domain deconvolution method filtered with a Gaussian wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 100 publications
(204 reference statements)
2
48
0
Order By: Relevance
“…Hansen et al () detected slow wave speed anomalies in the transition zone beneath Marie Byrd Land and suggested that this anomaly extended into the transition zone, but the anomalies were not well localized. Emry et al () investigated the thickness of the transition zone as a proxy for temperature, as the transition zone should be thinner in hot regions. They found evidence for higher temperatures beneath the northeast coast of Marie Byrd Land and also along the southern edge of West Antarctica, but not beneath central Marie Byrd Land.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al () detected slow wave speed anomalies in the transition zone beneath Marie Byrd Land and suggested that this anomaly extended into the transition zone, but the anomalies were not well localized. Emry et al () investigated the thickness of the transition zone as a proxy for temperature, as the transition zone should be thinner in hot regions. They found evidence for higher temperatures beneath the northeast coast of Marie Byrd Land and also along the southern edge of West Antarctica, but not beneath central Marie Byrd Land.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a thin conduit below the MBL anomaly could go undetected in our models; however, transition zone receiver functions do not indicate a mantle thermal anomaly beneath this region of MBL at transition zone depths [ Emry et al ., ]. Transition zone thinning, indicative of elevated mantle temperatures, is observed elsewhere in West Antarctica with the most significant beneath the MBL coast geographically northwest of station CLRK (Figure ), and thinning is also noted to a lesser extent beneath the Whitmore Mountains and the Bentley Subglacial Trench [ Emry et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The absolute P wave tomography has limited resolution but shows a region of slow velocities beneath MBL and part of the eastern WARS extending to ~800 km depth [ Hansen et al ., ]. However, little variation in transition zone thickness is reported beneath the region, suggesting that under normal mantle assumptions, there is no regional mantle thermal anomaly at depths greater than 400 km associated with this feature [ Emry et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…In WANT, Marie Byrd Land (MBL) is a prominent region of uplift, accompanied by extensive Cenozoic sub ice and subaerial volcanism (LeMasurier, ; Wörner, ). Geochemically, its magmas indicate the signature of a possible deep mantle source (Panter et al, ; Weaver et al, ; Wörner, ) yet a high‐temperature conduit extending into the deep mantle has not been definitely established (Emry et al, ; Hansen et al, ). The relationship between the WARS and MBL uplift is unclear (Behrendt & Cooper, ; Rocchi et al, ; Salvini et al, ).…”
Section: Tectonic Setting Of the Study Regionmentioning
confidence: 99%